Long-term decline of the canopy-forming algae Gelidium corneum, associated to extreme wave events and reduced sunlight hours, in the southeastern Bay of Biscay. (31st May 2018) - Borja, Angel; Chust, Guillem; Fontán, Almudena; Garmendia, Joxe Mikel; Uyarra, María C.
Abstract: Canopy-forming macroalgae are experiencing large biogeographical shifts due to climate change. One of them ( Gelidium corneum ) has shown a dramatic decline in biomass in northern Spain, in the past 20 years. We investigate here two most plausible hypotheses to explain its decline: (i) a combination of increasing wave energy and decrease of irradiance in the growth season; and (ii) a combination of increasing light in summer and decreasing nutrient concentration. Using a dataset of biomass and environmental variables (1993–2016), in three sectors and three water depths, we have determined that the variables explaining more biomass variability were: suspended solids, nitrate, sunlight hours, significant wave height threshold exceedances (Hs5m), temperature, silicate, and nitrite. When undertaking multiple regression analyses for the whole depth range, only the model including sunlight hours with Hs5m was selected, being highly significant (p < 0.0001) and explaining 37% of the variability. When comparing the macroalgal biomass between the initial period of the series (where the biomass was stable) and final period (showing biomass decline), 45% decrease was observed while the Hs5m increase was 41%, detaching the algae from the substratum during the growth season. The decline rate in biomass with time, at each sector and depth, was highly correlated (p < 0.001) to the wave energy flux received at each depth, which was higher at 5 m in all sectors, decreasing with depth. In turn, nutrients, instead of decreasing, have increased, and only nitrate presented a significant negative correlation with G. corneum biomass, which was not significant after detrending. The significant (p = 0.001) increase in rainfall over the studied period can explain the increase of those nutrients. Hence, we question whether the effect of nutrients is such, as already described. The most likely factor explaining the decline of this macroalga was the combination of sunlight hours decrease and Hs5m increase. Graphical abstract: Highlights: Gelidium algae biomass declined from 12000 to 1900 t in 20 years in Basque coast. Decline hypotheses include changes in SST, waves, irradiance, nutrients and others. A combination of wave increase and reduced sunlight hours is the most likely responsible. This finding has an effect on habitat prediction under climate change scenarios.